Systemic toxicity of topical corticosteroids - Jitender Jinagal; Parul Chawla Gupta; Rakesh Kumar Pilania; Jagat Ram (Indian Journal of Ophthalmology, 2019)
Corticosteroids are known to cause many ocular and systemic side effects when administered by oral or parenteral routes. Corticosteroid induced systemic toxicity secondary to topical steroid eye drops is rare. A 6-week-old, male infant was brought to our tertiary eye care center with bilateral congenital cataracts. The child underwent phacoaspiration with primary posterior capsulotomy without intraocular lens implantation in both eyes at an interval of 6 weeks. Child was initiated on topical betamethsone 0.1% eight times a day, tobramycin 0.3% six times a day, homatropine 2% twice a day, and carboxymethylcellulose 0.5% four times a day. Two and four weeks later he underwent surgical membranectomy in the right and left eye respectively followed by frequent use of topical steroids, initially given 1 hourly and then tapered weekly in the follow-up period. The patient showed increase in intraocular pressure and gain in body weight along with development of cushingoid habitus nearly 6 to 8 weeks after starting topical steroids. These side effects started weaning off following the reduction in dose of topical steroids, suggesting the role of the corticosteroid-related systemic side effects. This case highlights the serious systemic side effects secondary to increased frequency and duration of topical corticosteroid use in infancy. Hence, dosage of topical steroids should be adjusted in its therapeutic range to prevent their ocular and systemic side effects. Therefore, close monitoring is advocated for children using topical corticosteroids to prevent serious ocular and systemic side effects.